Sosialisasi Strategi Marketing Komunikasi dan Promosi Digital pada UMKM di Balai Latihan Kerja, Samosir dalam Menghadapi Destinasi Pariwisata Super Prioritas: Socialization of Marketing Communication Strategy and Digital Promotion to UMKM at the Work Training Center, Samosir in Facing Super Priority Tourism Destinations - Lamria Raya Fitriyani; Dewi Rachmawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
One of the programs is preparing the people on Samosir Island to become entrepreneurs in promoting traded products, namely the Pangururan Job Training Center (BLK), Samosir. The entrepreneur does not only need to have soft skill levels, namely materials for digital marketing and promotion strategies because they are supported by government programs that will make Lake Toba tourism develop into a Super Priority Tourism Destination (DPSP) as well as government programs that are targeting 30 million MSME Digitalization by 2024. MSME is believed to be able to improve the Indonesian economy, so socialization and material provided are needed to prepare MSME actors. This activity was carried out using the implementation method in the form of a pre-test, socialization, material provision, and a post-test to participants. The result of this activity is that the participants are motivated to develop their business, as well as an increased understanding of marketing communication and digital promotion strategies from the results of the pre-test and post-test given to participants so that participants can apply the material in businesses that are currently running or will be started.